Effectiveness of 3rd generation cephalosporin compare to 3rd generation cephalosporin - macrolides for community acquired pneumonia patients in PKU Muhammadiyah Yogyakarta Hospital - Muhammad Dwi Suprobo; Dyah Aryani Perwitasari; Irma Risdiana (Universitas Ahmad Dahlan, 2019)
Pneumonia is a lung infection caused by bacteria with high fever symptoms accompanied by cough with phlegm, shortness of breath. According to Riskesdas 2013 results, the prevalence of pneumonia based on diagnosis at Yogyakarta Special Region is 1.7% and 4.6%. The researcher has founds 172 adult patients diagnosed pneumonia during 2011-2016 in PKU Muhammadiyah Yogyakarta hospital. This study aims to determine the level of effectiveness between 3rd generation cephalosporins with 3rd generation cephalosporins and macrolides on the outcome of adult patients with pneumonia in PKU Muhammadiyah Yogyakarta hospital period 2015-2017. It was a retrospective cohort study with an affordable population. There were two groups of 3rd generation cephalosporins (n = 24) compared to the 3rd generation cephalosporins and macrolide (n = 13) measured results in the form of body temperature, shortness of breath, leukocyte count, and length of hospitalization using univariate and bivariate analyzes. Based on the results of the study, 70.3% was dominated by men, and 51.4% was dominated by the age group > 59 years. Both of groups showed a significant difference to the temperature where p=0.001 with difference of temperature decrease 0.79 ± 1.06 oC for single group while p=0.049 with difference of temperature decrease 0.65 ± 1.07 oC for combination group; as well as against leukocyte, both of groups had a value of p=0.001 where difference of leucocyte decrease was 4.80 ± 3.92 103/mm3 for single group and 5.43 ± 4.27 103 / mm3 combination group. While both of group showed no significant difference for shortness of breath p=0.638 with OR (95% CI) 2.4 (0.23 – 24.06) and p=0.435 for hospitalization, in single group was 5.88 ± 3.261 days while in combination group was 5.00 ± 1.826, this shows that the combination group had an average length of hospitalization of 0.88 days faster than the single group. The effectiveness between two groups showed a significant difference with p<0.05 on body temperature and leukocyte count. While both groups did not show a significant difference with p>0.05 to shortness of breath and length of stay.